MULTI HYDATID OF PAROTID BRAIN AND KIDNEY; REPORT OF A CASE - H. Emamy; GH. Bcheshti; SH. Shokoohi; SH Radjaieh; SH Mosavy (Tehran University of Medical Sciences, 1974)
An interesting case of rare multiple hydatid of parotid, brain and kidney is reported. She is a 35-year-old married woman first referred because of a swelling in the parotid region and later for neurological manifestions. On general physical examination, an abdominal mass was felt in the right hypochondrium. These multiple space-occupying 'lesions in the brain, kidney and parotid proved to be hydatid cyst. A short discussion on the classification of hydatid multiple localisation and the different ways that the parasite could reach different organs IS given and the control measures are highlighted.